2018
DOI: 10.3389/fmicb.2018.01622
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Sulfidic-Ice Microbial Communities, Borup Fiord Pass, Canadian High Arctic

Abstract: A sulfur-dominated supraglacial spring system found at Borup Fiord Pass (BFP), Ellesmere Island, Nunavut, Canada, is a unique sulfur-on-ice system expressed along the toe of a glacier. BFP has an intermittent flowing, subsurface-derived, glacial spring that creates a large white-yellow icing (aufeis) that extends down-valley. Over field campaigns in 2014, 2016, and 2017, numerous samples were collected and analyzed for both microbial community composition and aqueous geochemistry. Samples were collected from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 66 publications
(123 reference statements)
5
28
0
Order By: Relevance
“…was part of a consortium along with a Marinobacter sp. similar to what was found in previous samples at BFP (Gleeson et al, 2011; Trivedi et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…was part of a consortium along with a Marinobacter sp. similar to what was found in previous samples at BFP (Gleeson et al, 2011; Trivedi et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The research presented here identified sulfur-oxidizing genes in MAGs from different sites and site types at BFP, and across multiple different taxonomic lineages. Previous research at BFP identified (from both spring fluid and mineral deposits) a number of the same organisms found within our identified MAGs, including: Marinobacter, Loktanella (Grasby et al, 2003; Gleeson et al, 2011), and the sulfur oxidizers Sulfurimonas, Sulfurovum , and Sulfuricurvum (Gleeson et al, 2011, 2012; Wright et al, 2013; Trivedi et al, 2018). Our work has revealed that MAGs belonging to previously identified genera likely oxidize reduced sulfur compounds in addition to organisms that were not previously predicted to be taking part in such metabolic processes.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations